THE INFLUENCE OF PROJECT BASED LEARNING-STEM MODEL ON STUDENT LEARNING OUTCOMES - Akhmad Darmawan (JURNAL PENA SAINS, 2020)
This study aims to determine the project-based learning-STEM model's effect on biology learning outcomes in growth and development material. The learning was carried out in class XII IPA students of SMA Negeri 1 Muncar in the 2018/2019 academic year. This type of research is quasi-experimental research. The instrument in this study was a test given in the experimental class and the control class. The data were analyzed using parametric statistical analysis. There is a difference in the average post-test learning outcomes of the experimental class (PjBL-STEM model) with the control class's post-test learning outcomes using the independent sample t-test. The results of the analysis show that Sig. (2-tailed) of 0.00 0.05, which can be interpreted that there is a significant difference in the average student learning outcomes between the PjBL-STEM model (experimental class) and the conventional model (control class). The average post-test score of the experimental class with the PjBL-STEM model was 87.50, while the average score in the Control class was 79.82, so that there was an increase in the value of 7.68 in the experimental class. The PjBL-STEM model's application to improve learning outcomes can be continued with other materials that have STEM characteristics.